Penile traction therapy with the new device 'Penimaster PRO' is effective and safe in the stable phase of Peyronie's disease: a controlled multicentre study. (22nd November 2018) - Moncada, Ignacio; Krishnappa, Pramod; Romero, Javier; Torremade, Josep; Fraile, Agustin; Martinez‐Salamanca, Juan Ignacio; Porst, Hartmut; Levine, Laurence
Abstract : Objectives: To evaluate the efficacy and safety of a new penile traction device (PTD), 'Penimaster PRO', in a group of patients with stable Peyronie's disease (PD) compared with a non‐intervention group in a multicentre study. Material and Methods: A total of 93 patients with chronic stable PD (without erectile dysfunction, with no significant pain, and with a unidirectional curvature of at least 45° being stable for > 3 months) were recruited and followed for a 12‐week period. Of these patients, 47 were randomly assigned to the Penimaster PRO group (PG) and 46 to the non‐intervention group (NIG). Patients were asked to apply the PTD 3–8 h a day for 12 consecutive weeks, with specific instructions regarding the progressive increase of traction force applied to the penis over time. The primary outcome of the study was the change in the degree of curvature measured in the fully erect state after intracavernosal injection of alprostadil at baseline, 1, 2 and 3 months. Other variables, such as the type of curvature, stretched penile length (SPL), Peyronie's Disease Questionnaire (PDQ) scores, erectile function domain of the International Index of Erectile function (IIEF‐EF) score and adverse events (AEs) were also assessed in each visit. Results: Forty‐one patients in the PG and 39 in the NIG completed the study. There was an overall reduction in curvature of 31.2° ( P < 0.001) at 12 weeks compared to baseline in the PG, representing a 41.1% improvement from baseline, which significantly correlated with the number of daily hours the device was applied in a dose‐dependent manner. Those patients using the device < 4 h/day experienced a reduction of 15°–25° (mean 19.7°, 28.8% improvement; P < 0.05), while patients using the device > 6 h/day experienced greater curvature reduction, ranging from 20° to 50° (mean of 38.4°, 51.4% improvement; P < 0.001). In contrast, no significant changes in curvature were observed in the NIG. Furthermore, SPL increased significantly in the PG compared to baseline and compared with the NIG, ranging from 0.5 to 3.0 cm (mean 1.8 cm; P < 0.05). The IIEF‐EF score also improved in patients in the PG (by a mean of 5 points). Mild AEs occurred in 43% of patients, such as local discomfort and glans numbness. Conclusion: The use of the Penimaster PRO PTD, a non‐invasive treatment, should be offered to patients with stable PD for 3 consecutive months before performing any corrective surgery, as this provided a significant reduction in the curvature, an increase in penile length and a significant improvement of the symptoms and bother induced by PD.